Pengembangan Pariwisata di Badung Utara (Study kasus Kecamatan Petang Kabupaten Badung) - Setyawan, I Putu Gita; Dewi, Nyoman Diah Utari (Universitas Medan Area, 2024)
The tourism industry has an important role in the country's development. Apart from that, tourism also has an influence on Regional Original Income for Regional Governments. Indonesia is an archipelagic country located in Southeast Asia which is on the continent of Asia and the continent of Australia. Bali Island is the most popular tourist destination for local and international tourists. Based on Badung Regency Regulation No. 22 of 2021, it is stipulated that Agro Tourism is a tourist activity as an effort to increase tourist attraction by presenting agricultural activities as tourist activities. Petang District is located in the North Badung area with the iconic Tukad Benchung Bridge which is the highest bridge in Asia, making this area unique in its own right. Agro Techno Park is used as a center for the application of technology related to agriculture. As a forum for managing harvests. Apart from that, in terms of innovation to disseminate technology in agriculture, Agro Techno Park is directed as an area that can create an independent village and get positive value from the community and can grow the community's economic income. As we know in this tourist village, agriculture is an added value besides the scenery. The research uses a qualitative descriptive approach method, namely to get an in-depth picture of individual experiences in developing Agro-based tourism in North Badung.